Pelatihan Menggunakan Microsoft PowerPoint Sebagai Sarana Presentasi di SDN Subo 01 Pakusari Jember - Anisatul Rhodiah; Zaehol Fatah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
This community service activity was conducted to help elementary school students improve their digital literacy and basic presentation skills through Microsoft PowerPoint training at SDN Subo 01 Pakusari Jember. The training used a simple approach by combining short explanations with direct practice, allowing students to immediately try what they had learned, such as creating slides, adding text, inserting images, and using basic animations. The activity was carried out through several stages, including preparation, observation, implementation, and evaluation, and involved 22 fourth-grade students. The results showed that most students were able to understand and use PowerPoint better than before, even though some initially felt unfamiliar with the application. Around 70% of the participants were able to create simple presentations independently. In addition to improving technical skills, the training also helped students become more confident and active during the learning process. Based on the evaluation, most students expressed satisfaction with the activity, indicating that the training was useful and engaging for them.